The effect of good corporate governance and foreign ownership as a moderating variables on the board interlocking on financial performance - Natalie Winter; Werner Ria Murhadi; Mudji Utami (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2021)
The aims of this research is to analyze the effect of number of board interlocking, board size, family board participation, board independence, control variable such as firm size, firm age, and leverage, and moderate foreign ownership to number of board interlocking towards financial firm perfomance using ROA and Tobin’s Q as a proxy in non financial sector companies listed in Indonesia Stock Exchange (BEI) in period 2014-2018. This research uses quantitative approach with two least square regression analysis model. The sample used in this research is firms which are listed on the non financial in Indonesia Stock Exchange (IDX) on 2014-2018 period. The number of final samples used in this study were 366 business entities with 1830 observations. The findings result of this research indicate that concurrent commissioner positions have positive and significant effect towards ROA in non financial sector companies BEI on the period 2014-2018, while independent commissioners, family of commissioners, board size, and the interaction of multiple positions of commissioners with foreign ownership have insignificant effect towards ROA in non financial sector companies BEI on the period 2014-2018. Then variables independent commissioners, board size of commissioners, and the interaction of multiple positions of commissioner with foreign ownership have positive and significant effect towards Tobin’s Q in non financial sector companies BEI on the period 2014-2018, while the family of commissioners and concurrent commissioner positions have insignificant effect towards ROA in non financial sector companies BEI on the period 2014-2018.